2015
DOI: 10.1016/j.ijscr.2014.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset renal vein thrombosis: A case report and review of the literature

Abstract: INTRODUCTIONRenal vein thrombosis, a rare complication of renal transplantation, often causes graft loss. Diagnosis includes ultrasound with Doppler, and it is often treated with anticoagulation or mechanical thrombectomy. Success is improved with early diagnosis and institution of treatment.PRESENTATION OF CASEWe report here the case of a 29 year-old female with sudden development of very late-onset renal vein thrombosis after simultaneous kidney pancreas transplant. This resolved initially with thrombectomy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Both the fallopian tubes and ovaries are considered part of the uterine adnexa and lie within the contents of the iliac fossa [ 5 ]. Previously, we documented a case of an ovarian cyst compressing the renal vein of a grafted kidney in a young woman, ultimately causing renal vein thrombosis [ 2 ], and others documented intestinal obstruction caused by the fallopian tube [ 5 , 6 ]. Such rare but recurrent complications shed light on surgical approaches and female-specific considerations that need to be made intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the fallopian tubes and ovaries are considered part of the uterine adnexa and lie within the contents of the iliac fossa [ 5 ]. Previously, we documented a case of an ovarian cyst compressing the renal vein of a grafted kidney in a young woman, ultimately causing renal vein thrombosis [ 2 ], and others documented intestinal obstruction caused by the fallopian tube [ 5 , 6 ]. Such rare but recurrent complications shed light on surgical approaches and female-specific considerations that need to be made intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, urinary tract infections (UTIs) are among the most common bacterial infections occurring in transplant recipients [ 1 ]. We have previously reported the first case of a 29-year-old female with sudden development of late-onset renal vein thrombosis due to compression by an ovarian cyst [ 2 ]. Here, we present a 35-year-old female who underwent SPK transplantation complicated by strangulation of the renal vein and artery of the transplanted kidney by the fallopian tube.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable his PEs were due to compression of his blood vessels by his large left presumed myelolipoma which would increase the risk of thrombus formation. While this has not been reported as a complication of myelolipomas, it has been seen in patients due to ovarian cysts as well as adrenocortical carcinomas [ 5 ] . CAH due to 21OH deficiency itself is associated with an increased frequency of venothromboembolic events, although previous studies on the topic have suggested it may be a consequence of iatrogenic hypercortisolism from excess glucocorticoid replacement (which was not the case with this patient) [ 6 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing sensitivity of diagnostic imaging and interventional procedures have contributed to the success of graft salvage through interventional and medical, as opposed to surgical, means [4,10]. Catheter-directed infusion of thrombolytic agents such as TPA, streptokinase, and urokinase in patients with renal transplantation with stable grafts and no other contraindications to systemic thrombolytics [11,12] can be graftsaving. After thrombolysis, ongoing anticoagulation, usually with Heparin, is indicated, with the duration of anticoagulation dependent on identification of reversible or irreversible risk factors [11].…”
Section: Discussionmentioning
confidence: 99%